2019
DOI: 10.1093/jas/skz122.229
|View full text |Cite
|
Sign up to set email alerts
|

221 Optimizing sugar inclusion in high roughage diets for growing cattle

Abstract: Producers wishing to background cattle may not have access to grain in certain regions of the country or when grain price is high. Sugar sources may replace grain under these circumstances. The objective of this study was to determine optimum sugar concentration based on daily gain and feed conversion in high-forage diets fed to growing cattle. Ninety-two Angus crossbred (Ranch 1) steers (n = 60; 339 + 11 kg BW) and heifers (n = 32; 309 + 14 kg BW), and 89 Red Angus crossbred (Ranch 2) steers (338 + 16 kg BW) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…High-quality proteins like glutamic acid have been found to aid small intestinal starch digestion, and could be a beneficial inclusion in corn-based diets that would provide opportunity to increase intramuscular fat deposition ( Brake & Swanson, 2018 ; Moriel, 2018 ). Van der Wal, Zeltwanger and DiCostanzo, (2019) found that including a molasses-based urea supplement in backgrounding diets increased DMI but had no effect on ADG, resulting in decreased FCE. Therefore, sugar supplementation may replace corn in pasture based backgrounding to increase DMI of long fibre roughage.…”
Section: Backgroundingmentioning
confidence: 95%
“…High-quality proteins like glutamic acid have been found to aid small intestinal starch digestion, and could be a beneficial inclusion in corn-based diets that would provide opportunity to increase intramuscular fat deposition ( Brake & Swanson, 2018 ; Moriel, 2018 ). Van der Wal, Zeltwanger and DiCostanzo, (2019) found that including a molasses-based urea supplement in backgrounding diets increased DMI but had no effect on ADG, resulting in decreased FCE. Therefore, sugar supplementation may replace corn in pasture based backgrounding to increase DMI of long fibre roughage.…”
Section: Backgroundingmentioning
confidence: 95%